The Effect of Smoking Treatment on Infection Level, Dormancy, and Physiological Quality of Shallot Seed - Wariyanti Wariyanti; Leopold O. Nelwan; Sutrisno Sutrisno (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Plant-derived smokes has antimicrobial activity and have been reported to have the ability to promote germination for various kinds of plant seeds. The purpose of this study was to analyze the effect of coconut shell burning smoke against the level of fungal infection, dormancy, and the physiological quality of shallot seed bulb. The research design used was a factorial randomized block design. The first factor is the smoking time (t), with 3 levels of treatments (t1 = 40 minutes, t2 = 80 minutes, t3 = 120 minutes) and the second factor is the temperatures of the biomass reactor (T), with 2 treatments (T1 = 200 ± 50 oC and T2 = 300 ± 50 oC). The smoking process using the pyrolysis-external heating method was carried out without affecting the moisture content of the seeds. The smoking with reactor temperature of 300 oC and duration of 40 minutes gave the same effect as the treatment of the highest temperature and duration, two of these treatments gave the highest antimicrobial effect and dormancy compared to other treatments. The smoking with 300 oC reactor temperature and 40 minutes duration gave an average dormancy of 96.3±10.1 (DAH) and 50.7±1.8 % infection. Keywords:   Choconut shell smoke, Dormancy, Fungi infection, Physiological quality, Shallot seed bulbs